Analisis Trend Produksi Padi Organik dan Anorganik pada Lahan Rawa di Kabupaten Hulu Sungai Utara - Ahmad Suhaimi; Rezka Yulia (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2017)
This study aims to find out (i) fluctuations in production trends, (ii) forecasting projections, and (iii) volumes of organic and inorganic paddy production from 2016-2021 at wetland in Hulu Sungai Utara Regency. The study was conducted from March to July 2016. The research method used was descriptive with secondary data obtained from the Office of Food Crops and Horticulture of Hulu Sungai Utara Regency, data obtained from 2010 to 2015. The analysis used in this study was linear trend with the least squares method which aims to predict or predict the development of organic and inorganic rice production in swamps in North Hulu Sungai Regency, South Kalimantan Province. The results showed fluctuations in production trends, forecasting projections and production of organic and inorganic paddy each year has increased